Academic motivation and self-esteem in high school students of Ilo-Perú - Chana Ccama, Yesica (2024)
The purpose is to know if the variables academic motivation and self-esteem of the students present a relationship in the high school students of the I.E Almirante Miguel Grau Seminario of the province of Ilo, the study was carried out with 134 students, 78 women and 56 men, among 14 and 15 years old. The AMS-HS 28 Academic Motivation Scale and the Stanley Coopersmith Self-Esteem Inventory (SEI) school version questionnaires were used, the statistical inference used is Kendal's Tau C. The results in the confrontation of intrinsic motivation and the self-esteem dimensions of self and social are both high. Intrinsic motivation and self-esteem at home and at school are both at a low level. Academic motivation is at a medium level and self-esteem at a high level. It is concluded that there is no significant correlation between both variables, with p=0.070 > 0.05. It is stated that the levels of academic motivation do not represent significant changes in the self-esteem of students.